Prevalence, associates and stage-specific preventive behaviors of myopia among junior high school students in Guangdong province: health action process approach- and theory of planned behavior-based analysis - Miao ZHONG; Shao-min XU; Cai-jun SUN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the prevalence of myopia and its related personal eye habits among junior high school students and to explore stage-specific myopia prevention behaviors of the students based on health action process approach (HAPA) and theory of planned behavior (TBA).MethodsUsing stratified random cluster sampling, we recruited 4 894 students at 6 junior high schools in 5 prefectures of Guangdong province. An anonymous questionnaire survey was conducted among 2 289 students online and 2 570 students on-site during July 2020.ResultsOf the 4 859 students with valid responses, 3 013 (62.0%) reported being myopic and 994 (20.5%) reported suffering from myopia during past 6 months. The students being female, in higher schooling grade, and with parental myopia reported a significantly higher myopia prevalence rate than other students (P < 0.001 for all). The students' myopia prevalence differed significantly by sleeping time during school days, proper reading/writing time during school days or weekends, daily outdoor activity, outdoor activity in school days, outdoor activity with parents/friends during free days, posture while reading/writing, and rest time after continuous reading for 40 minutes (all P < 0.05). The results of multivariate logistic regression analysis revealed following risk factors of myopia for the students: being female, in higher schooling grade, with parental myopia, low frequency of outdoor activity for 2 hours per day, and low frequently of having a rest of 10 minutes after reading/writing for 40 minutes. Based on reported frequencies of having daily outdoor activity for at least 2 hours and having a rest of 10 minutes after reading/writing for 40 minutes, we classified 1 543 (31.8%), 1 433 (29.5%), and 1 883 (38.3%) of the students as at the pre-intention, intention, and action stage of developing eye habits for myopia prevention; high proportions of the boy students and the students in low schooling grade were assessed in the action stage. The students at the action stage reported a higher social cognition and better eye habits related to myopia prevention than the students at both pre-intention and intention stage (P < 0.01 for all) but no difference in risk cognition was observed among the students at different stages. The results of hierarchical regression analysis showed that for the students at pre-intention stage, the attitude towards and self-efficacy of action were major predictors for myopia prevention behaviors, jointly explaining 15% of total variance of behavior change; for the students at intention stage, risk perception, subjective norm, and action self-efficacy were major predictors, altogether explaining for 12% of total variance of behavior change; whereas, attitude towards action, subjective norm, action and coping self-efficacy, and behavioral planning and coping were major predictors, explaining 20% of total variance of behavior change, for the students at action stage.ConclusionAmong junior high school students, the prevalence of myopia varies with individual characteristic and eye habits; the influence of social cognition variables on myopia prevention behaviors is different among the students at various stages of developing eye habits for myopia prevention.